THE IMPACT OF FOCUSING STUDENTS' ATTENTION ON THEMSELVES AS FUTURE PROFESSIONALS ON THEIR PROFESSIONAL CALLING - Saveljeva, Regina; Rupšienė, Liudmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Researchers express ideas about the relationship between focusing students' attention on themselves as future professionals during their studies and students' professional calling. However, empirical evidence on this relationship is still lacking. The research aimed to answer the question: "What is the impact of focusing students' attention on themselves as future professionals on their professional calling?" In order to answer this question the quasi-experiment with the non-equivalent comparison group without the pre-test design has been carried out. The quasi-experimental programme was implemented in the experimental group of 31 student of the social pedagogy study programme of Klaipėda University in 2009-2014. The control group consisted of 79 students from three other Lithuanian universities. The final measurement was carried out in the control and experimental groups on May-June, 2014. The results argue that focusing students' attention on themselves as future professionals during their studies has an impact on their professional calling.